PENGARUH PENGGUNAAN MODEL IDEAL TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI GAYA BELAJAR PADA SISWA SMP TA’MIRUL ISLAM SURAKARTA - Anung Candra Lesmana; Ari Wibowo; Hardi Hardi; Heldy Ramadhan Putra Pembangunan (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
ABSTRACT Mathematical problem-solving skills are an essential competency in 21st-century learning; however, in practice, these skills are still not optimally achieved by many students. This condition requires the implementation of more effective learning models to improve problem-solving abilities, one of which is the IDEAL learning model. In addition, differences in students’ learning styles are assumed to influence learning outcomes and therefore need to be further examined. This study aims to determine the effect of the IDEAL learning model on students’ mathematical problem-solving abilities in terms of learning styles among eighth-grade students of SMP Ta’mirul Islam Surakarta in the 2025/2026 academic year. This research employed a quantitative method with a comparative approach. The sample consisted of 61 students selected using cluster random sampling, with class VIII A as the experimental group and class VIII C as the control group. The research instruments included a mathematical problem-solving test and a learning style questionnaire covering visual, auditory, and kinesthetic styles. Data analysis was conducted using prerequisite tests (normality and homogeneity) and a two-way ANOVA test. The results showed a significant difference between the IDEAL and non-IDEAL learning models on students’ mathematical problem-solving abilities, with a significance value of 0.008 < 0.05. The average score of the experimental group was 93.80, higher than the control group’s 89.67. Meanwhile, learning styles had no significant effect (Sig. = 0.581 > 0.05), and there was no significant interaction between learning models and learning styles (Sig. = 0.602 > 0.05). Kemampuan pemecahan masalah matematika merupakan keterampilan penting dalam pembelajaran abad ke-21, namun kenyataannya kemampuan ini masih belum optimal pada sebagian siswa. Kondisi tersebut menuntut adanya model pembelajaran yang lebih efektif untuk meningkatkan kemampuan pemecahan masalah, salah satunya model pembelajaran IDEAL. Selain itu, perbedaan gaya belajar siswa diduga turut memengaruhi hasil belajar sehingga perlu dikaji lebih lanjut. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran IDEAL terhadap kemampuan pemecahan masalah matematika ditinjau dari gaya belajar siswa kelas VIII SMP Ta’mirul Islam Surakarta Tahun Ajaran 2025/2026. Penelitian ini menggunakan metode kuantitatif dengan pendekatan komparatif. Sampel penelitian berjumlah 61 siswa yang dipilih melalui teknik cluster random sampling, terdiri atas kelas VIII A sebagai kelas eksperimen dan VIII C sebagai kelas kontrol. Instrumen yang digunakan berupa tes kemampuan pemecahan masalah matematika dan angket gaya belajar visual, auditori, dan kinestetik. Analisis data dilakukan dengan uji prasyarat (normalitas dan homogenitas) serta uji ANOVA dua jalur. Hasil penelitian menunjukkan terdapat perbedaan yang signifikan antara model pembelajaran IDEAL dan non IDEAL terhadap kemampuan pemecahan masalah matematika dengan nilai signifikansi 0,008 < 0,05. Rata-rata kelas eksperimen sebesar 93,80 lebih tinggi dibandingkan kelas kontrol sebesar 89,67. Sementara itu, gaya belajar tidak berpengaruh signifikan (Sig. = 0,581 > 0,05), dan tidak terdapat interaksi antara model pembelajaran dan gaya belajar (Sig. = 0,602 > 0,05).